A Note on Complementarity Over Time - Biswas, Tapan (Review of Economic Studies, 1976)
Journal Article A Note on Complementarity Over Time Get access Tapan Biswas Tapan Biswas University of Manchester Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 43, Issue 1, February 1976, Pages 179–181, https://doi.org/10.2307/2296611 Published: 01 February 1976 Article history Received: 01 May 1974 Accepted: 01 December 1974 Published: 01 February 1976